2021
DOI: 10.1007/s10067-021-05848-8
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary approach in the treatment of tendinous foot involvement in rheumatoid arthritis

Abstract: Introduction Patients with rheumatoid arthritis frequently consult for pain resulting from involvement of the tendons of the foot. This pain negatively affects foot biomechanics and quality of life. The most widely used treatment option for this condition is ultrasound-guided steroid injection, while other treatments were recommended such as heel pad, splints, and footwear. Objective To evaluate a joint intervention (rheumatology and podiatry) comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This has been concluded after the analysis of clinical and radiographic data [ 91 ]. In addition, these injections are effective in the treatment of tenosynovitis, especially if combined with foot orthoses, improving pain levels and functionality of the foot [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…This has been concluded after the analysis of clinical and radiographic data [ 91 ]. In addition, these injections are effective in the treatment of tenosynovitis, especially if combined with foot orthoses, improving pain levels and functionality of the foot [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on FPI in patients with RA frequently report greater pronation [6,21,28], increasing with the evolution of the disease. One of the causes that could influence our results is, once again, the exclusive localisation of pain in the forefoot, as it would discard diagnoses such as posterior tibial tendon dysfunction (PTTD), which is widely related to greater pronation [80], as well as the specific removal of pain in the M1 head. Makoto Hirao [81] found that the patients with greater pronation had a lower degree of central metatarsal pain since the pressure was rather focused on the M1 head.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis is an autoimmune disorder primarily affecting the joints. It causes inflammation and damage to the surrounding tissues, including the heels ( 7 ). Individuals with rheumatoid arthritis may be more susceptible to developing heel spurs.…”
Section: Medical Conditions Associated With Heel Spursmentioning
confidence: 99%